MUC1-C ACTIVATES THE BAF (mSWI/SNF) COMPLEX IN PROSTATE CANCER STEM CELLS - Hagiwara, Masayuki (Cancer Res, 2020)
The BAF (mSWI/SNF) chromatin remodeling complex is of importance in development and has been linked to prostate oncogenesis. The oncogenic MUC1-C protein promotes lineage plasticity in the progression of neuroendocrine prostate cancer (NEPC); however, there is no known association between MUC1-C and BAF. We report here that MUC1-C binds directly to the E2F1 transcription factor and that the MUC1-C→E2F1 pathway induces expression of embryonic stem cell esBAF components BRG1, ARID1A, BAF60a, BAF155, and BAF170 in castrate-resistant (CRPC) and NEPC cells. In concert with this previously unrecognized pathway, MUC1 was associated with increased expression of E2F1 and esBAF components in NEPC tumors as compared to CRPC, supporting involvement of MUC1-C in activating the E2F1→esBAF pathway with progression to NEPC. MUC1-C formed a nuclear complex with BAF and activated cancer stem cell (CSC) gene signatures and the core pluripotency factor gene network. The MUC1-C→E2F1→BAF pathway was necessary for induction of both the NOTCH1 effector of CSC function and the NANOG pluripotency factor, and collectively, this network drove CSC self-renewal. These findings indicate that MUC1-C promotes NEPC progression by integrating activation of E2F1 and esBAF with induction of NOTCH1, NANOG, and stemness.